ANALYSIS OF DIURNAL SEA SURFACE TEMPERATURE CHARACTERISTICS IN RELATION TO MADDEN-JULIAN OSCILLATION PROPAGATION CATEGORIES IN INDONESIAN MARITIME CONTINENT - Istiqomah, Fadhilatul
Madden-Julian Oscillation (MJO) can affect weather and climate variability in the Indonesian Maritime Continent. One of the factors that can initiate the occurrence of MJO is the diurnal sea surface temperature (SST). MJO propagation is not always the same, previous research has classified MJO into 4 categories: slow, fast, stand, and jump. Therefore, this study analyzes the characteristics of diurnal SST in relation to the four categories of MJO propagation in the Indonesian Maritime Continent. The data used in this study are spatio-temporal skin temperature data, interpolated outgoing longwave radiation (OLR), zonal winds and meridional winds. The calculation of diurnal SST in this study was carried out by calculating the difference between the maximum SST and minimum SST in one day. The characteristics of the diurnal SST pattern can be seen by calculating the difference between active and inactive MJO. Then the pattern is compared with the OLR variable pattern and surface wind speed. The difference in MJO propagation in the active phase has an effect on diurnal SST in the Indonesian Maritime Continent. The diurnal SST characteristics of each category are that the slow category is dominated by a negative difference of 93.72% with the strongest being in the Indian Ocean (95? E?105? E and 0??5? S) and in central Indonesia (115° E?140° E dan 5° N?15° S). The fast category has a negative difference of 73.44% which is located in the central part of Indonesia to the western Pacific Ocean (110? E?145? E and 5? N?15? S). The stand category has a positive difference that is quite dominant, approximately 47.31% and is located in the north of Indonesia, while the negative difference is in the south of Indonesia. The jump category has a fairly strong and evenly distributed positive difference in the north of Indonesia with a percentage of 32.58% and a strong negative difference in the south of Indonesia (95? E?140? E and 5? N?15? S). The diurnal SST pattern characteristics in each of these categories are consistent with the OLR variable pattern and surface wind speed.